THE EVOLUTION AND DISTRIBUTION OF THE EARLY PERMIAN GENUS URALOCERAS (AMMONOIDEA) - Bogoslovskaya M.F.; Boiko M.S. (My University, 2002)
Changes in the shell morphology (shell shape, size, ornamentation, and suture) of the genus Uraloceras in the Sakmarian and Kungurian are analyzed. The dynamics of species diversity within this genus and its spatial distribution are studied. Four stages in the evolution of the genus are recognized and described. The genus includes 33 species, of which four are new (U. omolonense and U. kolymense from the lower Artinskian of the Kolyma-Omolon Massif and U. bichense and U. posterum from the upper Artinskian of the Southern Urals).
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская